Measuring cognitive level using interactive map among secondary students: a quasi-experimental approach / Ernieza Suhana Mokhtar ...[et al.] - Mokhtar, Ernieza Suhana; Nasirun, Noraini; Syafiqah, Nurulsyazwani; Rosli, Rafiza (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
Spatial thinking is essential because it encourages the human mind to visualize and stimulate cognitive thinking, thus improving higher thinking order (HOTS). Unfortunately, it was found that the geography syllabus taught in secondary school is lacking this vital element. Hence, this study aims to assess the student cognitive level using an interactive map among secondary students in Geography subject. This study was underpinned by the Social Cognitive Theory (SCT). The cognitive level was measured using Bloom Taxonomy cognitive domain from low to high order thinking skills, namely knowledge, comprehension, application and analysis. Data were collected using a one-group pretest-posttest quasi-experimental design. The interactive map has been used as an intervention for the study. Pre-test and post-test questions were distributed before and after the intervention. 31 students of Sekolah Menengah Kebangsaan Arau participated in this study. Data were analysed using a paired t-test analysis. The result reveals the significant difference between cognitive domains among students. The interactive map increases their knowledge and analysis ability among students. This study contributes to the empirical evidence to the literature of SCT in the context of spatial thinking studies among secondary students in selected geography topics.